The Influence of Entrepreneurial Policy on Entrepreneurial Willingness of Students: The Mediating Effect of Entrepreneurship Education and the Regulating Effect of Entrepreneurship Capital - Zelin, Zhuo; Caihong, Chen; XianZhe, Chen; Xiang, Min (Frontiers in Psychology, 2021)
With the transformation and development of the social economy of the country, innovation, and entrepreneurship have been a wide concern in all sectors of the society. In contrast, the entrepreneurial success rate of college students in China is low, and the willingness of students to start a business is generally not high. As a leading element, entrepreneurship policy plays an important role in creating an enabling social environment for entrepreneurship and promoting innovation and entrepreneurship. The influence of entrepreneurship policy on the entrepreneurial will of college students is not only reflected in the improvement of entrepreneurship environment but also in the reform and development of innovation and entrepreneurship education in colleges and universities. This study conducted a survey of fresh graduates from 1,231 colleges and universities in 31 provinces across the country to examine the path and influence the mechanism of entrepreneurship policy on entrepreneurial willingness, and the subsequent regression analysis results show that the entrepreneurship policy and entrepreneurship willingness are positively related, and entrepreneurship education, as a “bridge,” presents a partial intermediary role in the relationship. In addition, the study also found that the entrepreneurship capital of college students has a moderating effect on the path of entrepreneurship education–entrepreneurship willingness, that is, the higher the entrepreneurship capital of students is, the higher the entrepreneurship willingness will be generated after they receive entrepreneurship education.